Numerical simulation of damage and failure in aircraft windshield structure against bird strike - Wang, F.S.; Yue, Z.F. (Materials in engineering, 2010)
Based on the updated Lagrangian approach, the incremented form of a damage-modified nonlinear visco-elastic constitutive model and its failure criterion were deduced using the updated Kirchhoff stress tensors and strain tensors. The finite element model of a windshield structure including windshield, framework, arc-frame, gasket and rivets was established, in which the adaptive contact relation and boundary condition was defined. A contact–impact coupling algorithm and the explicit dynamic finite element program LS-DYNA were applied to simulate the damage and failure process of windshield structure under three kinds of bird strike velocities. The damage-modified nonlinear visco-elastic constitutive model and its failure criterion were implemented into the user material program. The results showed that the damage and failure of windshield under bird strike can be effectively simulated.